2014
DOI: 10.4161/15592324.2014.977704
|View full text |Cite
|
Sign up to set email alerts
|

The effects of dopamine on antioxidant enzymes activities and reactive oxygen species levels in soybean roots

Abstract: In the current work, we investigated the effects of dopamine, an neurotransmitter found in several plant species on antioxidant enzyme activities and ROS in soybean (Glycine max L. Merrill) roots. The effects of dopamine on SOD, CAT and POD activities, as well as H 2 O 2 , O 2 ¡ , melanin contents and lipid peroxidation were evaluated. Three-day-old seedlings were cultivated in half-strength Hoagland nutrient solution (pH 6.0), without or with 0.1 to 1.0 mM dopamine, in a growth chamber (25 C, 12 h photoperiod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(13 citation statements)
references
References 35 publications
0
12
0
1
Order By: Relevance
“…Considering that exogenous dopamine inhibits root elongation in soybean seedlings (Guidotti, Gomes, Siqueira-Soares, Soares and Ferrarese-Filho, 2013), the shortening of roots due to increased hardness may be causally related to the dopamine levels. Alternatively, high dopamine may ameliorate stress imposed by ROS by acting as an antioxidant, similar to that observed with dopamine-treated soybean and apple roots (Gomes et al, 2014; Jiao et al, 2019).…”
Section: Discussionmentioning
confidence: 63%
“…Considering that exogenous dopamine inhibits root elongation in soybean seedlings (Guidotti, Gomes, Siqueira-Soares, Soares and Ferrarese-Filho, 2013), the shortening of roots due to increased hardness may be causally related to the dopamine levels. Alternatively, high dopamine may ameliorate stress imposed by ROS by acting as an antioxidant, similar to that observed with dopamine-treated soybean and apple roots (Gomes et al, 2014; Jiao et al, 2019).…”
Section: Discussionmentioning
confidence: 63%
“…Dopamine-induced elevation in superoxide dismutase activity and subsequent reduction in ROS levels and lipid peroxidation has been reported in soybean roots. 109 The antioxidative role of this biomolecule has been reported. 110 The allelopathic effect of dopamine has also been observed to be growth inhibitory for soybean roots.…”
Section: Metabolic Regulations Of Dopamine In Plants: Redox Signaling and Oxidative Stress Modulationmentioning
confidence: 99%
“…Also, in Rosaceae family, recent research has found that exogenous dopamine could regulate apple's drought resistance and salt tolerance by stomatal behavior (Li et al, 2015;Gao et al, 2020), as well as alleviate the drought-induced damages, replenishing of K, N, P, S, Cu and other trace elements (Li et al, 2015;Gao et al, 2020). Research about soybean even demonstrated that dopamine can affect the activity of antioxidant enzymes and the content of reactive oxygen species (ROS) in roots, thus enhancing the antioxidant activity in plants (Gomes et al, 2014).…”
Section: The Antioxidant Regulation Of Dopaminementioning
confidence: 99%